The a and (a, b)-Analogs of Zagreb Indices and Coindices of Graphs. (27th October 2011) - Mansour Mansour, Toufik Toufik; Song Song, Chunwei Chunwei
Abstract : The first and second Zagreb indices were first introduced by Gutman and Trinajstić (1972). It is reported that these indices are useful in the study of anti-inflammatory activities of certain chemical instances, and in elsewhere. Recently, the first and second Zagreb coindices, a new pair of invariants, were introduced in Došlić (2008). In this paper we introduce the a and (a, b )-analogs of the above Zagreb indices and coindices and investigate the relationship between the enhanced versions to get a unified theory.